Differential glioma-associated tumor antigen expression profiles of human glioma cells grown in hypoxia. - Lisheng Ge (PLoS ONE, 2012)
Human U251 and D54 glioma cells were tested for expression of 25 glioma-associated tumor antigen precursor proteins (TAPP) under hypoxic (1% O(2)) or normoxic (21% O(2)) conditions. Hypoxic glioma cell lines increased their mRNA expression for nine TAPP (Aim2, Art-4, EphA2, EZH2, Fosl1, PTH-rP, Sox 11, Whsc2 and YKL-40), as assessed by quantitative reverse transcriptase real-time/polymerase chain reaction (qRT-PCR). Increased differences with three hypoxic-induced TAPP: EZH2, Whsc2 and YKL-40 were shown at the protein levels by fluorescent antibody staining and quantitative electrophoretic analysis. Two TAPP (MRP3 and Trp1) were down-regulated by hypoxia in glioma cell lines. Growing the glioma cells under hypoxia for 13 days, followed by returning them back to normoxic conditions for 7 days, and restored the original normoxic TAPP profile. Thus, hypoxia was an environmental factor that stimulated the transient expression of these antigens. Intracranial xenografts grown in nude mice derived from U251 cells that had been cultured under neurosphere stem cell conditions showed increased expression of Whsc2 or YKL-40, demonstrating that these in vitro properties of glioma also occur in vivo. Whsc2-specific cytotoxic T lymphocytes killed the hypoxic U251 glioma cells better than normoxic glioma cells. The antigens expressed by hypoxic tumor cells may be a better source of starting tumor material for loading dendritic cells for novel immunotherapy of glioma using tumor-associated antigens.